Comparative analysis of the state of supporting tissues when using different orthopedic structures for immediate loading on dental implants in case of tooth loss on one of the jaws - Proshchenko, А. М.; Proshchenko, Н. С.; Vefelev, С.Ю. (Actual Dentistry, 2024)
Abstract. The use of fixed prosthetic structures supported by implants in case of partial or complete tooth loss remains relevant. Thanks to the use of intraoral welding of temporary prosthesis elements, the method of manufacturing temporary prosthetic structures has been integrated into the practice of prosthetic dentistry, which allows them to be fixed during dental implantation surgery. The aim of the study is to compare the condition of supporting tissues when using different orthopedic structures for immediate loading on dental implants in case of partial or complete loss of teeth in one of the jaws. For the comparative evaluation of different orthopedic structures on implants for immediate loading, temporary structures made of polymethyl methacrylate, composite structures reinforced with metal beams using intraoral welding, acrylic structures with dentures reinforced with a cast beam were selected. Computed tomography and orthopantomography were used to assess the condition of the bone tissue before implantation, 3 days and 1, 6, months after implantation. The study resulted in the following conclusions. Restoration of complete tooth loss in one of the jaws with fixed orthopedic composite structures reinforced with metal beams using intraoral welding is a promising method that allows to reduce the time of patient rehabilitation, the number of surgical stages and the trauma of the surgical stage of treatment. In this regard, soft and bone tissue trophism is less disturbed, which affects the subsequent osseointegration and functioning of implants. At the same time, the risks of bone resorption are minimized. Clinical evaluation of the tissues around the implants and X-ray analysis of the bone in patients with acrylic structures with set teeth reinforced with cast metal beams showed almost similar results. However, the technique involves additional surgical intervention, which negatively affects the trophism and healing of soft and bone tissues, increases the risk of complications, and extends the rehabilitation period. The use of temporary structures made of polymethyl methacrylate is less appropriate due to their less stable fixation, which can lead to inflammation of the soft tissues surrounding the implants and bone resorption. Keywords: fixed structures, occlusal relations of the jaws, digital technologies, dental implantation.